Importance of Proper Waste Management Programme in Edo State, Nigeria - Olikiabo, Samuel Osaretin; Erhabor, Norris Igbinosa (NIU Journal of Social Sciences, 2025)
Health care facilities are established to provide treatment and safeguard the health of the people against conditions that pose risk or threat to health care providers, patients, waste handlers and the entire community. Health care activities are carried out to protect, restore health and save lives but paradoxically, they are known to generate wastes that poses obvious health risks either by direct infection or through exposure to dangerous chemicals and radiation materials. The purpose of the study was to determine the medical waste management practice in health care facilities in Edo State. Eight research questions were raised to guide the study while six hypotheses were formulated and tested at 0.05 level of significance. The population for the study comprised the 1,383 health care facilities in Edo State. A sample size of 276 respondents was selected using the multi-stage sampling technique. The instrument used was a validated Dichotomous scale format questionnaire with 29 items. The instrument’s reliability was established using the test-retest method of estimating reliability and a co-efficient value of 0.68 was obtained. Data generated from the study were analyzed using descriptive statistics of frequency count, percentage and inferential statistics of binomial test and chi-square. The findings revealed that some health care facilities still do not fully comply with the dictates of approved practices specifically in the areas of segregation, incineration method, use of water proof floor with good drainage, treatment modalities and that there was no absolute difference in the urban and rural settings in terms of medical waste management. It was concluded that the immense benefits of proper waste management should be fully utilized in compliance with the approved practices to avert the possibility of accidents and disease outbreak that could result in loss of life and property. It was recommended that health care facilities should improve practices at all the stages of waste management. Therefore, all health care facilities owe a duty to protect the public and the environment and should have peculiar responsibilities as regard the waste they produce in a sanitary manner to reduce infection and illness.